Supercapacitors with neutral aqueous electrolytes - Chae, Jung Hoon (2014)
Fossil fuels, which are the main energy sources of the current world, are running low and alternative ways of generating and storing different types of energies are becoming daunting missions. Renewable energy is very attractive because the source of the energy is often free and also environmentally friendly. The key issue to utilise the renewable energies in sustainable manner is how effectively store the energies and provide them on demand. Therefore, the significance of the energy storage devices has been widely recognised in recent time.